Fast And Accurate Receiver Jitter Tolerance Extrapolation Using The Q-Factor Linear Fitting Method - Abdul Rahim, Abdul Rais (2017)
A performance bit rates of more than 6 Gb/s is deemed as a common standard in high-speed interconnect system in conjunction with the recent enhancement of high-speed serial interface (HSSI). In industry, receiver (Rx) jitter tolerance (JTOL) measurement required to characterize the high-speed interconnect. Time required for conventional methods to complete Rx JTOL measurement for low bit error rate (BER) values normally took a week’s time depending on the data rate. In addition, a large number of bits is required to be transmitted hence resulting measurement cost as inefficient. This research project implements a method known as Q-factor linear fitting method to reduce the measurement time of the Rx JTOL at low BER by using high BER data. The result shows that the measurement of Rx JTOL using Q-factor linear fitting method using BER 10-10 data achieved 11x speed-up in comparison to direct measurement of Rx JTOL. The proposed methods of combined different level of BER values and increase more data points of higher BER able to significantly improve the accuracy of the Rx JTOL measurement result. The proposed method is successfully established in the experiment where the results obtained indicated relative error of Rx JTOL using Q-factor linear fitting method of BER 10-10 data are reduced from 9.47% to 3.31% after combining with the BER 10-11 data and relative error for Rx JTOL extrapolation measurement using BER 10-10 data at low temperature (-25˚C) is reduced from 9.47% to 5.43% by increasing the measurement data point from 20 data points to 30 data points